Retracted: Risk of cardiovascular disease among diabetic patients in rural population of Central India - Singh, Prem S.; Zafar, K. S.; Kumar, Manoj; Yadav, Sudhir K. (International Journal of Research in Medical Sciences, 2017)
The article titled “Risk of cardiovascular disease among diabetic patients in rural population of Central India” by Singh PS published in International Journal of Research in Medical Sciences 2017;5(4):1563-70, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20171266 is retracted. After the publication of the above article, one of the publishers reported that a large part of the text is plagiarized from a similar article published in Journal of Anthropology, Volume 2014, Article ID 421439, 9 pages, http://dx.doi.org/10.1155/2014/421439 (Mary Grace Tungdim, T. Ginzaniang, G. Poufullung Kabui, Deepali Verma, Satwanti Kapoor. Risk of Cardiovascular Disease among Diabetic Patients in Manipur, Northeast India). We contacted the author who could not satisfactorily respond to our queries. Since the author could not satisfactorily defend his paper and contravened the declaration he made while submitting his manuscript, it was decided to retract the article from International Journal of Research in Medical Sciences and not to consider any manuscript submitted by him in future.